Gaze behavior in golf putting - A review - Ziv, G.; Lidor, R. (International Journal of Golf Science, 2019)
Gaze behavior in general, and the quiet eye (QE) in particular, are integral to the performance of closed, self-paced motor tasks. This review examines the relationship between the QE (and a number of other gaze properties) and golf-putting performance. An analysis of 26 studies revealed conflicting results. For example, while some studies showed that longer QE durations (QEDs) (e.g., 2-3 sec) characterize expert golfers, successful putting performance, and improved learning, several other studies reported no relationship between QEDs and putting performance. Four out of six studies (66.7%) showed that experts have longer QEDs on the ball, five out of eight studies (62.5%) showed longer QEDs in successful versus unsuccessful putts, four out of five studies (80%) found that QE may explain 14-43% of the variance in performance, and five out of six studies (83.3%) showed that QE can be trained and will lead to improved putting performance. We discuss some inconsistencies in the reviewed data, and outline a number of methodological concerns and research limitations associated with the reviewed studies, including (a) a lack of studies on different QE locations, (b) a lack of studies that directly manipulate QEDs, and (c) the failure of most studies to calculate QED for each phase of the putt. We also propose a number of applications for practitioners who teach golfers how to putt.